6. PERKIRAAN NILAI EKONOMIS AKIBAT PENYAKIT ORF PADA KAMBING DI TIGA PASAR HEWAN KABUPATEN ACEH BESAR (Estimation of the Economic Value Resulted by Orf Disease on Goat in Three Livestock Market in Aceh Besar District) - Adhona Bhajana Wijaya Negara (Jurnal Medika Veterinaria, 2016)
This study aims to determine the prevalence and economic value of goats infected with orf traded in 3 livestock markets in Aceh Besar district, which is Seulimum, Sibreh, and Ulee Kareng livestock market. This method used the cross-sectional observational study. The population in this study was all of goat sellers, while the goat sample was selected using simple random sampling technique. The questionnaire was filled by using interview techniques to the respondents who selected by purposive sampling. Diagnosing of orf disease in goats was performed by looking at the possibility of the presence of clinical symptoms, afterward the data were included into recording sheets. Data were analyzed by descriptive analytic. The results showed that the prevalence of the orf disease in 3 livestock markets in Aceh Besar district was 3.4%, and the economic value of goats infected with orf was below 1,500,000 rupiah. The conclusion of this study is the price of goat infected with orf tend to be lower than the healthy one, thus the profit also low. ____________________________________________________________________________________________________________________ Key words: prevalence, economic value, orf infection